2022
DOI: 10.3389/fenvs.2022.888171
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Ecotoxicological Effects of Perfluorooctanoic Acid (PFOA) and Perfluorohexanoic Acid (PFHxA) on Freshwater Microbial Community

Abstract: The ubiquitous presence of perfluorinated carboxylic acids (PFCAs) around the globe has attracted increasing attention, due to their persistency, bioaccumulation, and toxicity. Nevertheless, the ecotoxicological effects of the compounds on aquatic microorganisms has remained understudied. Hence, the present study focused on determining, and comparing, the effects of regulated long-chain PFCA, perfluorooctanoic acid (PFOA), and nonregulated short-chain PFCA, perfluorohexanoic acid (PFHxA), on the diversity, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In recent decades, major studies on the toxicological effects of perfluoroalkyl substances have focused on two of the first legacy compounds discovered, PFOS and PFOA, that are the most representative molecules for perfluoroalkyl sulfonic acids (PFSAs) and perfluoroalkyl carboxylic acids (PFCAs), respectively [50][51][52][53][54]. Laine et al [55] addressed, beside PFOA, PFHxA as a potential ecotoxicological compound for the freshwater microbial community. Statistical analysis showed that both PFOA and PFHxA at elevated doses considerably modified the composition of the microbial community.…”
Section: Toxic Effects Of Pfas In Organismsmentioning
confidence: 99%
“…In recent decades, major studies on the toxicological effects of perfluoroalkyl substances have focused on two of the first legacy compounds discovered, PFOS and PFOA, that are the most representative molecules for perfluoroalkyl sulfonic acids (PFSAs) and perfluoroalkyl carboxylic acids (PFCAs), respectively [50][51][52][53][54]. Laine et al [55] addressed, beside PFOA, PFHxA as a potential ecotoxicological compound for the freshwater microbial community. Statistical analysis showed that both PFOA and PFHxA at elevated doses considerably modified the composition of the microbial community.…”
Section: Toxic Effects Of Pfas In Organismsmentioning
confidence: 99%
“…PFHxA is a short-chain member of a subgroup of PFASs called perfluoro carboxylic acids (PFCAs) that is water soluble. Toxicity information on such short-chain molecules is scarce and hence it is still unclear whether these compounds are a safe long-term alternative for the long-chain PFASs in terms of environmental and human health [12]. Here, using a rigorous, family-based study design, we evaluate the differences in intra class correlation (ICC) of larval photomotor response and gene expression between full-sibling families based on different levels of PFHxA exposures.…”
Section: Introductionmentioning
confidence: 99%